Diversity of bacteria in a full-scale petrochemical wastewater treatment plant experiencing stable hydrocarbon removal. (June 2018) - Behnami, Ali; Farajzadeh, Davoud; Isazadeh, Siavash; Benis, Khaled Zoroufchi; Shakerkhatibi, Mohammad; Shiri, Zohreh; Ghorghanlu, Sajjad; Yadeghari, Adeleh
Abstract: Bacteria play a main role in biological wastewater treatment plants (WWTP). Herein, bacterial diversity was characterized in a full-scale WWTP treating petrochemical wastewater containing a wide range of hydrocarbons. Diversity analysis of the activated sludge was carried out using culture-dependent and culture independent methods. From a total of 20 bacterial species identified using 16S rRNA sequence analysis, Brevibacillus parabrevis, Cloacibacterium normanense and Sphingopyxis soli were described for the first time from a petrochemical WWTP. The Shannon diversity index as a measure of bacterial diversity showed decreases from 3.181 to 2.614 during warm and cold seasons. The dominant phyla in all samples was Proteobacteria comprised 63% of the total isolates. Overall, the results showed that the diversity of bacterial communities was higher in warm months rather than cold months. Although, volatilization has usually a significant role on the removal of volatile organics such as phenol, benzene, toluene, and styrene from the liquid phase, the presence of isolated bacterial species indicates their contribution in removal process. Thus, further studies on the capabilities of isolated bacteria in degradation of specific pollutants will be helpful to deepen scientific understanding of biological treatment of difficult wastewaters.